Comportamiento de pilotes sometidos a carga lateral - Reese, Lymmon (My University, 1979)
Piles must often support substantial lateral loads as well as axial loads. Examples of pile-supported structures wich must support large lateral loads include marine structures, large advertising signs and transmission towers.
Keywords: soil; rotation; analysis; program; porcedure